2022
DOI: 10.1177/09622802221095244
|View full text |Cite
|
Sign up to set email alerts
|

Response-adaptive treatment randomization for multiple comparisons of treatments with recurrent event responses

Abstract: Recurrent event responses are frequently encountered during clinical trials of treatments for certain diseases, such as asthma. The recurrence rates of different treatments are often compared by applying the negative binomial model. In addition, a balanced treatment-allocation procedure that assigns the same number of patients to each treatment is often applied. Recently, a response-adaptive treatment-allocation procedure has been developed for trials with recurrent event data, and has been shown to be superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Gao developed a response-adaptive treatment-allocation procedure to compare efficacy between two treatments in trials with recurrent event data, which was shown to be superior to balanced treatment allocation [16]. Further, the procedure was improved for both pairwise comparisons and many-to-one comparisons [17]. As mentioned previously, many-to-one comparisons are often considered in dose response studies, especially in the early drug development process, where different dosage levels need to be compared with a control simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Gao developed a response-adaptive treatment-allocation procedure to compare efficacy between two treatments in trials with recurrent event data, which was shown to be superior to balanced treatment allocation [16]. Further, the procedure was improved for both pairwise comparisons and many-to-one comparisons [17]. As mentioned previously, many-to-one comparisons are often considered in dose response studies, especially in the early drug development process, where different dosage levels need to be compared with a control simultaneously.…”
Section: Introductionmentioning
confidence: 99%